(untitled) (Journal of the College of Basic Education, 2024)
Praise be to God, and prayers and peace be upon the most honorable messengers and upon his good and pure family. Abu Dalama is considered one of the poets of the first Abbasid era who were not fortunate enough to occupy sufficient status among modern critics, as these critics used to study what was known and famous among the people, such as Al-Mutanabbi, Al-Hutay’ah, Bashar bin Burd, and others. They are that the matter of our poet remained limited to a few pieces of news and narrations that were transmitted by some historical books and preserved for us as a lamp that illuminates the way for us. Abu Dalama was not a young poet as some think, but rather he was a stalwart and a scholar of Arab poetry in his time, especially in the field of humor. He was able, with his artistic ability and poeticism, to His uniqueness, quick wit, and presence are rare for him to be the founder of the school of humor, sarcasm, and sarcasm, accompanied by his contemporaries of poets of humor and immorality, such as Abu al-Sham.